Manajemen Nyeri dengan Teknik Relaksasi Autogenik dan Aromaterapi Pada Lansia dengan Hipertensi - Lisdahayati, Lisdahayati; Pome, Gunardi; Harsanto, D. Eka; Putri, Sisilia (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Hypertension in the elderly is often accompanied by chronic pain that affects their quality of life, requiring safe and effective pain management interventions. This study aimed to evaluate the effectiveness of autogenic relaxation techniques and aromatherapy in reducing pain in elderly individuals with hypertension. A descriptive case study design was used with two elderly clients in the working area of UPTD Sukaraya Public Health Center, Baturaja Timur District, over two weeks. Data were collected through interviews, observations, and documentation. The results showed a reduction in pain scale from 6 to 4 for Client I and from 4 to 3 for Client II after the intervention. In addition, the clients' blood pressure significantly decreased, and improvements were noted in sleep quality and daily activities. In conclusion, the combination of autogenic relaxation techniques and aromatherapy is effective in reducing pain intensity in elderly individuals with hypertension. It is recommended to integrate this technique into nursing care practices and conduct further research with a larger sample size.